CURRENT APPROACHES TO MANAGEMENT OF MULTIPLE PREGNANCIES - L. G. Sichinava (IRBIS LLC, 2016)
A clinical lecture presents the current management of multiple pregnancies, modern diagnostics and treatment of complications in this high risk group of patients. A different approaches to management of multiple pregnancies according to chorionicity, early diagnosis of specific complications is necessary for improving neonatal outcomes.